Topographies of Fascism : Habitus, Space, and Writing in Twentieth-Century Spain. - Santianez, Nil (Toronto Iberic., 2013)
Topographies of Fascism offers the first comprehensive exploration of how Spanish fascist writing - essays, speeches, articles, propaganda materials, poems, novels, and memoirs - represented and created space from the early 1920s until the late 1950s.